Characterization and discrimination of fermented sweet melon juice by different microbial strains via GC-IMS-based volatile profiling and chemometrics - Zhaoling Wang; Si Mi; Xianghong Wang; Kemin Mao; Yuwei Liu; Jie Gao; Yaxin Sang (Food Science and Human Wellness)
The main purpose of this study was to investigate the effect of different lactic acid bacteria and yeast strains on the volatile composition of fermented sweet melon juice. Headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) coupled with chemometrics was performed to identify the potential volatiles for the discrimination of different fermented sweet melon juice. In total, 70 volatile compounds were found in the fermented sweet melon juices. Of them, 45 compounds were annotated according to the GC-IMS database and classified into esters, alcohols, aldehydes, ketones and furans. Results from the multivariate analysis reveal that sweet melon juice fermented by different combinations of microbial strains could be distinctly separated from each other. A total of 15 volatiles with both variable importance in projection value > 1 and P < 0.05 were determined as potential markers for the discrimination of fermented sweet melon juice. This study confirms the effect of microorganisms on the flavor of the fermented sweet melon juice and shows the potential of HS-GC-IMS combined with chemometrics as a powerful strategy to obtain volatile fingerprints of different fermented sweet melon juice.